2012
DOI: 10.1038/onc.2012.293
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutation of Brca1 alters the fate of mammary luminal cells and causes luminal-to-basal mammary tumor transformation

Abstract: Breast cancer developed in familial BRCA1 mutation carriers bears striking similarities to sporadic basal-like breast tumors. The mechanism underlying the function of BRCA1 in suppressing basal-like breast cancer remains unclear. We previously reported that the deletion of p18(Ink4c) (p18), an inhibitor of G1 cyclin Ds-dependent CDK4 and CDK6, stimulates mammary luminal progenitor cell proliferation and leads to spontaneous luminal tumor development. We report here that germline mutation of Brca1 in p18-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(98 citation statements)
references
References 66 publications
8
90
0
Order By: Relevance
“…Indeed, the receptor status of the metastasis may be more predictive of response to therapy. One small study showed that, although 74% of patients with ER-positive primary tumours whose recurrent tumours retained ER expression responded to endocrine therapy, only 12% of patients with ER-positive primaries and ER-negative metastases likewise responded [8]. Similar discordances between hormone receptor content of primary breast cancer versus metastasis have also been recently documented in several other studies [16,17] and loss of ER was associated with a significantly shorter median survival.…”
Section: Solitary Hypothalamus Triple Negative Metastasis From Luminamentioning
confidence: 58%
See 1 more Smart Citation
“…Indeed, the receptor status of the metastasis may be more predictive of response to therapy. One small study showed that, although 74% of patients with ER-positive primary tumours whose recurrent tumours retained ER expression responded to endocrine therapy, only 12% of patients with ER-positive primaries and ER-negative metastases likewise responded [8]. Similar discordances between hormone receptor content of primary breast cancer versus metastasis have also been recently documented in several other studies [16,17] and loss of ER was associated with a significantly shorter median survival.…”
Section: Solitary Hypothalamus Triple Negative Metastasis From Luminamentioning
confidence: 58%
“…Basal-like cancers have a poor prognosis and are not amenable to treatment with either endocrine therapy or trastuzumab because they are hormone receptor-negative and do not show HER2 overexpression or amplification. It has recently been reported the implication of BRCA-1 loss of function in this subtype of breast cancer [8]. Our patient was tested for BRCA 1 and BRCA-2 genes and they didn't show any significant mutation pattern.…”
Section: Solitary Hypothalamus Triple Negative Metastasis From Luminamentioning
confidence: 67%
“…19,20 To directly determine the role of loss of function of Brca1 in controlling MECs, we used Brca1 f/¡ ;MMTVCre (Brca1 f/¡ ;MC) mice, in which MMTV-cre is active in virgin epithelia and mammary glands from these mice express <5% of Brca1 protein and mRNA relative to the levels in Brca1 f/C ;MC mice, as we described previously. 19,27 We compared p16 expression in Brca1 (Fig.…”
Section: Deletion Of Brca1 In Mammary Epithelium Results In Senescencmentioning
confidence: 99%
“…20,27 Primary antibodies used are as follows: p16 (Santa Cruz Biotechnology), Ki67 (Novocastra Laboratories, Newcastle upon Tyne, UK), gH2AX (Cell Signaling). The IACUC (Institutional Animal Care and Use Committee) at the University of Miami approved all procedures.…”
Section: Histopathology Immunohistochemical Stainning and Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation